The Impact of Minority Representation at Mortgage Lenders - FRAME, W. SCOTT; HUANG, RUIDI; JIANG, ERICA XUEWEI; LEE, YEONJOON; LIU, WILL SHUO; MAYER, ERIK J.; SUNDERAM, ADI (Journal of Finance, 2025)
ABSTRACT We study links between the labor market for loan officers and access to mortgage credit. Using novel data matching mortgage applications to loan officers, we find that minorities are underrepresented among loan officers. Minority borrowers are less likely to complete mortgage applications, have completed applications approved, and to ultimately take up a loan. These disparities are reduced when minority borrowers work with minority loan officers. These pairings also lead to lower default rates, suggesting minority loan officers have an informational advantage with minority borrowers. Our results suggest minority underrepresentation among loan officers reduces minority borrowers’ access to credit.